2014
DOI: 10.1111/xen.12143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commercial ELISA and RIA for measuring porcine C‐peptide: implications for research

Abstract: Porcine C-peptide concentration can be reliably measured in porcine serum samples with either assay (ELISA or RIA). However, the C-peptide results generated by these two assays are not equivalent. Therefore, assay bias must be considered before directly comparing pre-clinical studies that used either of these assays. We determined that harmonization between the assays is appropriate in a specific concentration range. Outside of that range, we do not know whether a linear correction function can be more broadly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…As we reported previously, a low bias was observed in the ELISA results using the RIA standards; conversely, a high bias was observed in the RIA results using the ELISA standards …”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…As we reported previously, a low bias was observed in the ELISA results using the RIA standards; conversely, a high bias was observed in the RIA results using the ELISA standards …”
Section: Resultssupporting
confidence: 75%
“…Similarly, RIA data can be transformed, the slope was 0.4930±0.0456 (95% CI, 0.4882‐0.4977), and the intercept, −0.0456±0.0063 (95% CI, −0.0581 to −0.0332). Recommended correction factors to effectively harmonize comparisons between the previous RIA with the new ELISA in NHP serum matrix are presented in Table ; porcine matrix is presented for comparison …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the level of agreement between the RIA and enzyme‐linked immunosorbent assay (ELISA) that is available as a replacement, Graham et al. evaluated the serum C‐peptide concentrations in 60 landrace pigs at fasting and glucose challenge. The authors concluded that comparison of RIA and ELISA measurements of the same sample was not equivalent but within a linear range, the assays may correlate.…”
Section: Methodsmentioning
confidence: 99%